Caste, land ownership and agricultural productivity in India: evidence from a large-scale survey of farm households. Issue 4 (19th May 2021) - Khan, Md Riyazuddin; Haque, Mohammad Imdadul; Zeeshan; Khatoon, Noorsaba; Kaushik, Isha; Shree, Karuna
ABSTRACT: This article examines the relationship between caste, land ownership and agricultural productivity in India, utilising data from a large-scale survey of farm households. Access to resources like information, technology, inputs, markets, and support institutions are important for sustainable and inclusive growth of agriculture. The results indicate that socially disadvantaged households (Scheduled Castes and Scheduled Tribes) have lower access to land and also other resources, but they produce more output per unit of land because they are more diversified towards high-value crops that generate more returns and are labour intensive. This calls for policy emphasis on crop diversification in the agricultural sector.